Penerapan Model Pembelajaran Learning Cycle 5E untuk Meningkatkan Kemampuan Komunikasi Matematis dan Keaktifan Belajar Siswa SMP - Sukmaliah, Mamah (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2015)
The research was grounded by the results of previous research which showed thatmathematical communication ability and learning activity students are not as expected. One of modelslearning for enhancing mathematical communication ability is Learning Cycle 5E.The purpose of thisresearch is to comprehensively describe the enhancement of students’ mathematical communicationability and learning activity as a result of learning cycle 5E. This research is a quasi-experiment withclassroom action research study that applies two learning models; learning cycle 5E and ekspositorilearning. Population of this research ia all student in SMP Negeri 22 Bandung. Sampling used bypurposive sampling, VIII represent as sampling. Research instruments are mathematicalcommunication tes, scale and observation sheet. Data analysis is based on the whole student. Theresult obtained are: 1) learning by using models learning cycle 5E on the subject of the circle canimprove the student mathematical communication ability ; 2) Activity of students who were thaughtunder learning cycle 5E is better than activity of students who were taught under expository learning:3) students’ mathematical communication ability who were thaught under learning cycle 5E is betterthan who were taught under expository learning; 4) students' attitudes toward learning mathematics byusing modellearning cycle 5E is positive. Therefore, the study of mathematics by using model learningcycle 5E can be used as an alternative model of learning in an effort to improve students' mathematicalcommunication ability